Analisis Kinerja Keuangan pada Perusahaan BUMN Subsektor Pertambangan Logam dan Mineral Menggunakan Metode EVA dan MVA - Calvin Wijaya; Kartika Yuliantari; Nurhidayati Nurhidayati; Sugiyah Sugiyah (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
Several companies including metal and mineral mining subsector state-owned companies have carried out various strategies to ensure performance goes well. This research is useful for knowing the calculation of financial performance through financial statement analysis. This research uses non-statistical quantitative methods. Secondary data sources of financial statements using EVA and MVA methods that can be accessed through the official IDX and company websites. Sampling using purposive sampling method which uses several criteria. The results of the calculation of EVA three companies in 2020 - 2023 in a row are positive, which means that adding value to the company's capital costs results in an income figure above zero (>0) in other words there is no minus. While the results of the calculation of one company in 2022 are negative, which means that they do not add value to the company's capital costs, resulting in income below zero (>0) in other words there is no minus.